Taboo Comedy Television and Controversial Humour - Bucaria, Chiara; Barra, Luca.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
The essays in this collection explore taboo and controversial humour in traditional scripted (sitcoms and other comedy series, animated series) and non-scripted forms (stand-up comedy, factual and reality shows, and advertising) both on cable and network television. Whilst the focus is predominantly on the US and UK, the contributors also address more general and global issues and different contexts of reception, in an attempt to look at this kind of comedy from different perspectives. Over the last few decades, taboo comedy has become a staple of television programming, thus raising issues concerning its functions and appropriateness, and making it an extremely relevant subject for those interested in how both humour and television work. .
1.Taboo Comedy on Television: Issues and Themes. Chiara Bucaria and Luca Barra -- Part I.Controversial Humour in Comedy and Drama Series -- 2.The Rise and Fall of Taboo Comedy in the BBC. Christie Davies -- 3.The Last Laugh: Dark Comedy in U.S. Television. Kristen A. Murray -- 4.'This Is Great, We're Like Slave Buddies!': Cross-Racial Appropriation in 'Post-Racial' TV Comedies. Carter Soles -- 5.Phrasing!: Archer, Taboo Humor and Psychocanalytic Media Theory. Matt Sienkiewicz -- 6.Taboo Humanity: Paradoxes of Humanizing Muslims in North-American Sitcoms. Kyle Conway -- Part II. Controversial Humour in Variety Shows, Commercials and Factual Programming -- 7.Dummies and Demographics: Islamophobia as Market Differentiation in Post-9/11 Television Comedy. Phil Scepanski -- 8.Excessive Stand-Up, the Culture Wars, and '90s TV. Evan Elkins -- 9.Tosh.0, Convergence Comedy, and the 'Post-PC' TV Trickster. Ethan Thompson -- 10.Crude and Taboo Humour in Television Advertising: An Analysis of Commercials for Consumer Goods. Elsa Simões Lucas Freitas -- 11.Filthy Viewing, Dirty Laughter. Delia Chiaro -- 12.A Special Freedom: Regulating Comedy Offence. Brett Mills .
Keywords: Motion picture acting; Film genres; Comedy; Genre